2011
DOI: 10.1016/j.jcrs.2011.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of cataract surgery after bag-in-the-lens intraocular lens implantation following ISO standard 11979-7:2006

Abstract: The BIL IOL met the ISO criteria; that is, primary PCCC was safe in healthy eyes and in eyes with ocular comorbidities and no eye developed PCO over a mean follow-up of 26.1 ± 21.3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 30 publications
2
28
0
2
Order By: Relevance
“…A long-term study would be particularly useful to provide information on the IOL material stability because hydrophilic IOLs may have calcification. The occurrence of calcification is nevertheless low: in a study of 806 cases of IOLs with the same 26% hydrophilic acrylic raw material as the POD FineVision IOL, Tassignon et al 27 reported only two cases of calcification.…”
Section: Discussionmentioning
confidence: 99%
“…A long-term study would be particularly useful to provide information on the IOL material stability because hydrophilic IOLs may have calcification. The occurrence of calcification is nevertheless low: in a study of 806 cases of IOLs with the same 26% hydrophilic acrylic raw material as the POD FineVision IOL, Tassignon et al 27 reported only two cases of calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating the OCT into the operating microscope opens the possibility of viewing the space of Berger in real time. In this article, we report the first results of a new real-time intraoperative OCT technique to image the space of Berger while performing a planned posterior capsulorhexis for bag-in-the-lens (BIL) cataract surgery [22]. …”
Section: Introductionmentioning
confidence: 99%
“…The demographic characteristics of the cohort are summarized in table 2. The mean age of the patients was 68 years ± 11.2 which was comparable with the mean age of 65.0 years ± 18.3 in the largest reported cohort of BIL surgical patients [16]. Summaries of the duration of diabetes, HbA1c and blood pressures, where obtainable, were included.…”
Section: Resultsmentioning
confidence: 76%
“…BIL cataract extraction was performed as previously described [16]. Briefly, after performing a calibrated 5-mm anterior rhexis, a standard phacoemulsification technique was used to remove the lens material.…”
Section: Methodsmentioning
confidence: 99%